Synthesis and Characterization of Ni/Al Layered Double Hydroxides Composite Based-Material with Chitosan, Cellulose, and Graphene Oxide - Amri Amri; Zaqiya Artha Zahara; Patimah Mega Syah Bahar Nur Siregar; Zulkarnain; Alfan Wijaya (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2024)
In this study, the synthesis of composite materials produced from Ni/Al with three types of carbon-based materials namely chitosan (Ch), cellulose (Ce), and graphene oxide (GO) was successfully carried out supported by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), and Brunauer-Emmett-Teller (BET) analysis. The combined characteristics of the two starting materials are present in the composite material based on XRD and FT-IR data. The surface area of Ni/Al-LDH increased after compositing with Ch, Ce, and GO, from 3.3 m2/g to 9.5 m2/g in Ni/Al-Ch, 5.1 m2/g in Ni/Al-Ce, and 78.4 m2/g in Ni/Al-GO. These findings indicate that the materials are suitable for various applications such as photocatalytic and adsorption as effective materials in further research.